2006
DOI: 10.1007/s11270-006-2194-0
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Alkylated Polycyclic Aromatic Hydrocarbons in a Crude Oil-Contaminated Soil

Abstract: Phytoremediation uses plants and their associated microorganisms in conjunction with agronomic techniques to remove or degrade environmental contaminants. The objective of the field study was to evaluate the effect of vegetation establishment plus fertilizer addition on the biodegradation of alkylated polycyclic aromatic hydrocarbons in a crude oil-contaminated soil. Four replications of the following treatments were used: non-vegetated non-fertilized control; fescue (Lolium arundinaceum Schreb.) − ryegrass (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(57 citation statements)
references
References 36 publications
0
53
1
3
Order By: Relevance
“…In a related study, Campbell, Paquin, Awaya, and Li (2002) noted that using industrial hemp (Cannabis sativa) in treating PAHs contaminated soil, led to reduced concentrations of benzo(a)pyrene and chrysene. Recent advances in phytodegradation studies have come to light in the application of rye grass (Lolium multiflorum) and bermudagrass (Cynodon dactylon) in degrading alkylated two ring naphthalenes (White, Wolf, Thoma, & Reynolds, 2006). In their contribution on distribution of PAHs in sub-cellular root tissue, Kang, Chen, Gao, and Zhang (2010) and Ward, Singh, and Van Hamme (2003) had revealed that using L. multiflorium, pyrene was most adsorped in the root of the plant than other PAHs.…”
Section: Phytodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related study, Campbell, Paquin, Awaya, and Li (2002) noted that using industrial hemp (Cannabis sativa) in treating PAHs contaminated soil, led to reduced concentrations of benzo(a)pyrene and chrysene. Recent advances in phytodegradation studies have come to light in the application of rye grass (Lolium multiflorum) and bermudagrass (Cynodon dactylon) in degrading alkylated two ring naphthalenes (White, Wolf, Thoma, & Reynolds, 2006). In their contribution on distribution of PAHs in sub-cellular root tissue, Kang, Chen, Gao, and Zhang (2010) and Ward, Singh, and Van Hamme (2003) had revealed that using L. multiflorium, pyrene was most adsorped in the root of the plant than other PAHs.…”
Section: Phytodegradationmentioning
confidence: 99%
“…Other studies in this regard include anaerobic digestion and ozonation (Bernal-Martínez, Carrière, Patureau, & Delgenè, 2005), biodegradation and modified Fenton reagent (Nam, Rodriguez, & Kukor, 2001), biological, chemical and electrochemical treatment (Zheng, Blais, & Mercier, 2007) as well as Fenton reagent versus ozonation (Goi & Trapido, 2004). A growing body of data have been reporting on the use of combined vegetation establishment with chemicals in degradation of PAHs (White, Wolf, Thoma, & Reynolds, 2006;Pan et al, 2009;White, Wolf, Thoma, & Reynolds, 2006) reported that a combination of L. arundinacum and L. multiflorum mixture with fertilizer successfully degraded two rings PAHs such as naphthalene. In a separate study, Pan et al (2009) had observed that B. napus degraded PAHs in humic acid environment.…”
Section: Combined Degradationmentioning
confidence: 99%
“…Plants in phytoremediation of hydrocarbon contaminants have been proposed to improve degradation conditions in soil (Kuiper et al, 2004), and some improvement in biodegradation has been observed in plant microcosms/microecosystems (Miya and Firestone, 2000). Plant-associated microbes, especially in the root zone, potentially play a central role in rhizoremediation (Parrish et al, 2004;White et al, 2006) because plants mediate a rhizosphere effect illustrated by plant-specific microbial communities (Smalla et al, 2001;Costa et al, 2006). Generally, the rhizosphere of plants harbours a higher diversity of bacteria than the surrounding bulk soil due to root exudates and oxygen that stimulate bacteria (Briones et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing plants to absorb, accumulate and detoxify contaminants in the growth substrate through physical, chemical or biological processes is a wide spread practice (eg. White, et al, 2006;Jilani and Khan, 2006). This technology has been applied to both organic and inorganic pollutants present in soil (solid substrate), water (liquid substrate) or the air (Ghosh and Singh, 2005).…”
Section: Introductionmentioning
confidence: 99%